Central Nervous System Tuberculosis: An Imaging Perspective. Issue 2 (May 2017) - Chaudhary, Vikas; Bano, Shahina; Garga, Umesh Chandra
The increasing prevalence of tuberculosis in both immunocompetent and immunocompromised individuals in recent years makes the disease a topic of universal concern. It has insidious onset and can affect virtually any organ system in the body, including the central nervous system (CNS). CNS tuberculosis (TB) is becoming more and more complex and atypical with onset of multidrug-resistant TB. Routine diagnostic techniques using serology and body tissue are time consuming and may delay the definitive management. Hence, it is important to be familiar with various radiologic features of CNS TB to ensure early and accurate diagnosis, thereby reducing high morbidity and mortality associated with the disease. The newer imaging techniques further help to improve the characterization and diagnosis of atypical CNS TB. The authors review the imaging characteristics of different forms of CNS tuberculosis involving the brain and spine and discuss the role of advanced imaging modalities in differentiating CNS TB from other disease process.